Wnt/β-catenin signaling pathway in the tumor progression of adrenocortical carcinoma - Tai, Yanghao; Shang, Jiwen (Frontiers in Endocrinology, 2024)
Adrenocortical carcinoma (ACC) is an uncommon, aggressive endocrine malignancy with a high rate of recurrence, a poor prognosis, and a propensity for metastasis. Currently, only mitotane has received certification from both the US Food and Drug Administration (FDA) and the European Medicines Agency for the therapy of advanced ACC. However, treatment in the advanced periods of the disorders is ineffective and has serious adverse consequences. Completely surgical excision is the only cure but has failed to effectively improve the survival of advanced patients. The aberrantly activated Wnt/β-catenin pathway is one of the catalysts for adrenocortical carcinogenesis. Research has concentrated on identifying methods that can prevent the stimulation of the Wnt/β-catenin pathway and are safe and advantageous for patients in view of the absence of effective treatments and the frequent alteration of the Wnt/catenin pathway in ACC. Comprehending the complex connection between the development of ACC and Wnt/β-catenin signaling is essential for accurate pharmacological targets. In this review, we summarize the potential targets between adrenocortical carcinoma and the Wnt/β-catenin signaling pathway. We analyze the relevant targets of drugs or inhibitors that act on the Wnt pathway. Finally, we provide new insights into how drugs or inhibitors may improve the treatment of ACC.